2010
DOI: 10.2478/v10042-008-0091-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of I-TAC-binding receptors CXCR3 and CXCR7 in proliferation, activation of intracellular signaling pathways and migration of various tumor cell lines.

Abstract: Chemokines and its receptors stimulate tumor growth, migration and invasion. In this study we evaluated the expression and function of CXCR3 and CXCR7 receptors in cervical carcinoma, rhabdomyosarcoma and glioblastoma cell lines. We found that both receptors were expressed at different degree by tumor cells. CXCR7 was expressed at both mRNA and protein level by all tumor cell lines. The expression of CXCR7 differed between rhabdomyosarcoma subtypes. The receptor was highly expressed in alveolar rhabdomyosarcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
2
18
0
1
Order By: Relevance
“…Similar results have been obtained for different tumors (19,22,23,28). GAs are able to inhibit the expression of MAPK and AKT kinases which were shown previously to be involved in activating the motility of tumor cells (26,27). Thus, parallel blocking of MET receptor expression and activation of kinases involved in cell migration by GAs could be responsible for observed inhibition of GBM migration and invasion after HGF stimulation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar results have been obtained for different tumors (19,22,23,28). GAs are able to inhibit the expression of MAPK and AKT kinases which were shown previously to be involved in activating the motility of tumor cells (26,27). Thus, parallel blocking of MET receptor expression and activation of kinases involved in cell migration by GAs could be responsible for observed inhibition of GBM migration and invasion after HGF stimulation.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, using real-time RT-PCR and flow cytometry, we showed that GBM cells express the MET receptor and that HGF stimulates the phosphorylation of MAPK and AKT kinases in GBM cells, two kinases involved not only in tumor growth but also in tumor cell migration (26,27). Moreover, we have shown that GAs can downregulate the surface expression on MET receptor.…”
Section: Discussionmentioning
confidence: 67%
“…However, recent investigations have shown that CXCR7 can signal via β-arrestin (30) resulting for example in CXCL12-dependent activation of MAP-kinase in interneurons in vivo (31), and MAP-kinase and Akt pathways in primary rat astrocytes and Schwann cells (14) and human glioblastoma cell lines (16). Furthermore, the second ligand for CXCR7, CXCL11 can also induce activation of MAP-kinase and Akt signaling pathways (32) and has chemotactic properties on vascular smooth muscle cells (30). Examples of the reported effects of CXCL12 via CXCR7 are chemotaxis in T lymphocytes (12), angiogenesis and invasion in hepatocellular carcinomas, while metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…DU-145 cells cultured at a density of 900 cells/mm 2 in DMEM-F12 HAM supplemented with 10% FbS for 24 h were treated with the medium containing 100 µM fenofibrate or 100 µM perhydrol (positive control) in the presence of fluorescence ROS indicator DHR 123 (dihydorhodamine 123; 1:500, Sigma) for 4 h. Measurements of DHR 123 fluorescence intensity were carried out using a bD FACSCanto™ cytometer, and the data were analyzed using the winMDI 2.8 program (29). A total of 10 5 cells was analyzed for each series.…”
Section: Methodsmentioning
confidence: 99%